2022
DOI: 10.3389/fimmu.2022.1007080
|View full text |Cite
|
Sign up to set email alerts
|

A minimally-edited mouse model for infection with multiple SARS-CoV-2 strains

Abstract: Efficient mouse models to study SARS-CoV-2 infection are critical for the development and assessment of vaccines and therapeutic approaches to mitigate the current pandemic and prevent reemergence of COVID-19. While the first generation of mouse models allowed SARS-CoV-2 infection and pathogenesis, they relied on ectopic expression and non-physiological levels of human angiotensin-converting enzyme 2 (hACE2). Here we generated a mouse model carrying the minimal set of modifications necessary for productive inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The hybrid human/mouse ACE2 knock-in model introduced herein contributes substantially to the extant limited array of mouse models capable of physiological ACE2 expression under the regulation of endogenous Ace2 promoter elements, which are susceptible to multiple SARS-CoV-2 variants. This model exhibits distinct attributes concerning the number and localization of substituted amino acids and the iterations of CRISPR–Cas9-mediated editing, setting it apart from previously established models 41 44 . Subsequent comparative studies are imperative for a rigorous assessment of infection susceptibility and disease progression across these disparate models.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid human/mouse ACE2 knock-in model introduced herein contributes substantially to the extant limited array of mouse models capable of physiological ACE2 expression under the regulation of endogenous Ace2 promoter elements, which are susceptible to multiple SARS-CoV-2 variants. This model exhibits distinct attributes concerning the number and localization of substituted amino acids and the iterations of CRISPR–Cas9-mediated editing, setting it apart from previously established models 41 44 . Subsequent comparative studies are imperative for a rigorous assessment of infection susceptibility and disease progression across these disparate models.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of murine ACE2 (M.musculus) is possible with the N501Y substitution in spike [16-18], and we indeed observed increased infection with the Alpha, as well as the other N501Y encoding RBDs from Beta, Gamma, and BA1 spikes (Fig 7B). Previous studies have shown that Asn501 is largely incompatible with rodent ACE2 His353, as murine ACE2 with a H353K mutation can restore infection with virus encoding Asn501 RBD [19]. Human ACE2 with a K353H substitution reduces infectivity with Asn501 RBD virus [20], and the N501Y change circumvents these incompatibilities.…”
Section: Plos Pathogensmentioning
confidence: 97%
“…Infection of murine ACE2 ( M.musculus ) is possible with the N501Y substitution in spike [1618], and we indeed observed increased infection with the Alpha, as well as the other N501Y encoding RBDs from Beta, Gamma, and BA1 spikes ( Fig 7B ). Previous studies have shown that Asn501 is largely incompatible with rodent ACE2 His353, as murine ACE2 with a H353K mutation can restore infection with virus encoding Asn501 RBD [19]. Human ACE2 with a K353H substitution reduces infectivity with Asn501 RBD virus [20], and the N501Y change circumvents these incompatibilities.…”
Section: Sars-cov-2 Variant Infectivity With Ace2 Orthologsmentioning
confidence: 99%